Lithofacies-genetic characteristics of sedimentary basins in the foreland of the Pomeranian Stage in the Drawsko Lakeland (northern Poland) - Paluszkiewicz, Ryszard; Paluszkiewicz, Renata (Quaestiones Geographicae, 2011)
The research carried out in the years 1995-98 in the area of the Złocieniec proglacial lake inclined its authors to take a broader view of the operation of proglacial basins in the Drawsko Lakeland (Paluszkiewicz 2004). Glaciolacustrine deposits in the studied lakeland area were discovered by Maksiak and Mróz in 1978. Until that time, the varved deposits at Złocieniec had not been subjected to lithological analysis. The more detailed studies conducted by the present authors in the years 2006-2007 at both Złocieniec and Wierzchowo sites with the help of geo-engineering methods allowed them to show that the two sites with varved clays in this region should be treated as separate sedimentary basins. The basins differ in thickness of varved deposits, in size, and processes responsible for the formation of the rhythmically stratified series.